Fixed Points of Generalized Contractive Maps - Abdou AfrahAN; Latif Abdul (Fixed Point Theory and Applications, 2009)
We prove some results on the existence of fixed points for multivalued generalized -contractive maps not involving the extended Hausdorff metric. Consequently, several known fixed point results are either generalized or improved.